Examination of Gene Loss in the DNA Mismatch Repair Pathway and Its Mutational Consequences in a Fungal Phylum. (23rd September 2021) - Phillips, Megan A; Steenwyk, Jacob L; Shen, Xing-Xing; Rokas, Antonis
Abstract: The DNA mismatch repair (MMR) pathway corrects mismatched bases produced during DNA replication and is highly conserved across the tree of life, reflecting its fundamental importance for genome integrity. Loss of function in one or a few MMR genes can lead to increased mutation rates and microsatellite instability, as seen in some human cancers. Although loss of MMR genes has been documented in the context of human disease and in hypermutant strains of pathogens, examples of entire species and species lineages that have experienced substantial MMR gene loss are lacking. We examined the genomes of 1, 107 species in the fungal phylum Ascomycota for the presence of 52 genes known to be involved in the MMR pathway of fungi. We found that the median ascomycete genome contained 49/52 MMR genes. In contrast, four closely related species of obligate plant parasites from the powdery mildew genera Erysiphe and Blumeria, have lost between five and 21 MMR genes, including MLH3, EXO1, and DPB11 . The lost genes span MMR functions, include genes that are conserved in all other ascomycetes, and loss of function of any of these genes alone has been previously linked to increased mutation rate. Consistent with the hypothesis that loss of these genes impairs MMR pathway function, we found that powdery mildew genomes with higher levels of MMR gene loss exhibit increased numbers of mononucleotide runs, longer microsatellites, accelerated sequence evolution, elevated mutational bias in the A|T direction, and decreased GC content. These results identify a striking example of macroevolutionary loss of multiple MMR pathway genes in a eukaryotic lineage, even though the mutational outcomes of these losses appear to resemble those associated with detrimental MMR dysfunction in other organisms.